The Relationship Between Islamic Values And Malays Travel Behaviour - Azmi, Noor Azam (2018)
Malay is one of the many races living in Malaysia, and the Malays enjoy a long history of travelling. The traditional travel culture of the Malays is known by the term “merantau”, and to date, the Malays are actively engaged in travelling activities. The story of Panglima Awang's voyage and Munshi Abdullah's adventure are evidences of the greatness of the Malays travelers (known as “Musafir” in Arabic Language). Before Islam, the Malays behavior was much shaped by the traditional and cultural beliefs in addition to flavoured by other religions philosophy. After Islam, the Malays behavior is shaped in accordance to the wishes of ALLAH the Al-Mighty, and their travel behavior is no exception. The current scenario shows that a number of tourist destinations failed to provide comfort to the Malay travellers. The concerns, for example, involve the impractical prayer space facilities, irrespective of “halal” issues especially food-related and indifferent attitude towards immoral activities. In general, this study seeks to see the influence of demographics and travel characteristics on Malays travel behaviour, to which extent do the Malays aware of Islamic belief in relation to travel, to what level do the Malays practice the Islamic belief related to travel, how the Islamic belief related to travel affects the Malays travel behavior, and to identify the Malays travel behaviour. According to the Theory of Reasoned Action (TRA), three aspects (namely 'Belief', 'Attitude' and 'Intention') will influence the behaviour and therefore, this study employed this theory to examine how belief, attitude and intention in Islam religion influence the Malays travel behaviour.